The Role of Servant Leadership in Organizational Behavior of Employees in Non-Profit Organizations: An Applied Study on Charitable Societies in the Regions of Riyadh and Qassim at Kingdom of Saudi Arabia - Aljarbou, Raghad; Alshenaifi, Najla (The Arab Journal of Administration, 2024)
The study aimed to identify the role of servant leadership in the organizational behavior of employees in non-profit organizations in the Kingdom of Saudi Arabia. The study followed the descriptive survey method, and a questionnaire was used to collect data, and the sample in this study amounted to (382) people from employees of charitable societies in the regions of Riyadh and Qassim, including managers, employees, and volunteers. The results of the study concluded that there is a direct correlation with a statistical significance at the level (0.05) between the total degree of servant leadership and the total degree of organizational behavior of employees in non-profit organizations, where the correlation coefficient reached (0.323). So, the study found there is a positive relationship with a statistical significance between the total degree of servant leadership and the dimensions of organizational behavior for employees in non-profit organizations (in-role performance, helping behavior, creative behavior), while there isn’t a relationship between servant leadership and the deviant behavior of employees in the non-profit sector. The study recommends training leaders in the arts of dealing with employees through the establishment of appropriate training programs, and the importance of direct communication between the leader and workers to listen to them and solve their problems. It also recommends the necessity of setting plans, clarifying the tasks and responsibilities of the employees, directing them to the goals of the organization, encouraging them to have a social spirit, educating them to adhere to the rules of job conduct and work ethics, urging them to cooperate, and creating creative and innovative ways of working.